CONDITIONAL DISCONTINUANCE OF CRIMINAL PROCEEDINGS AS A PENAL MEASURE IN THE FISCAL PENAL CODE - Sebastian Kowalski (Probacja)
The study contains an analysis of the legal nature of conditional discontinuance of criminal proceedings against perpetrators of fiscal offences. The aim of the research is to determine whether conditional discontinuance of criminal proceedings included in the Fiscal Penal Code as a penal measure is the same means of criminal-legal reaction to a prohibited act as conditional discontinuance of criminal proceedings regulated in the Criminal Code as a probation measure, or whether it has a different character. The research will be conducted using the dogmatic-legal method, i.e. based on the analysis of the normative text, as well as the doctrinal and case-law output of the Supreme Court - with a clear emphasis on the autonomy of fiscal penal law. The peculiar nature of this area of law undoubtedly has an impact on the possibility of "transferring" to the Fiscal Penal Code the appropriately applicable provisions of the Criminal Code, including those concerning the prerequisites for conditional discontinuance of criminal proceedings and the obligations that may be imposed on the perpetrator of a fiscal offence. The conclusions of the research focus on the conclusion that conditional discontinuance of criminal proceedings in a fiscal offence case meets all the conditions of a probationary measure, although it clearly differs in terms of the prerequisites for its adjudication and probationary obligations from conditional discontinuance of proceedings in a offence case. Above all, it is not a measure to prevent and combat petty crime, and the regulation of conditional discontinuance of criminal proceedings related to the victim does not have a raison d'être in fiscal crime cases. This is a consequence of the separation of fiscal criminal law as a special field of criminal law. By making it possible, on the one hand, to maintain the status of an unpunished person and, on the other hand, by providing for the realisation of the enforcement purpose of the fiscal offence proceedings, the legislator makes conditional discontinuance of proceedings with respect to the perpetrator of a fiscal offence a valuable alternative to other institutions serving the degression of punishment. All the more so, as it may also be applied in the event of imputation of a fiscal offence punishable by imprisonment.